Characterization of native bee species and their biocultural relationship in the Oaxacan Mixteca - Vásquez-García, Adela; Sangerman-Jarquín, Dora Ma.; Schwentesius Rindermann, Rita (Revista Mexicana de Ciencias Agrícolas, 2021)
There are more than 20 000 species of bees, only 5% are social, within these is the Meliponini tribe, for Mexico 46 species of native stingless bees are reported (Arnold et al., 2018). These native bees carry out fundamental tasks since they are great pollinators, they are responsible for the maintenance and balance of the ecosystem. Currently there is evidence on the negative effects on bees due to the various actions of man that have caused their decrease, among them traditional agriculture and the extraction of wild nests stand out. The objective of this study was to characterize the native bee species and their biocultural relationship with the community of Peña Flor de Clavo, Santa Lucia Monteverde, Oaxaca, where semi-structured interviews were applied to the inhabitants to know the native bee species, the sources of food, knowledge, uses and practices of local management. A total of 11 species of stingless bees and 10 genera were identified, eight species are recognized locally, which are: Frieseomelitta nigra, Geotrigona acapulconis, Melipona fasciata, Nannotrigona perilampoides, Scaptotrigona hellwegeri, Trigona fulviventris, Partamona bilineata and Trigonisca pipioli and three species are unknown.
Keywords: food sources; native bees; species characterization